The role of gender and anxiety in the association between somatic diseases and depression: findings from three combined epidemiological studies in primary care. (9th November 2017) - Asselmann, E.; Venz, J.; Pieper, L.; Wittchen, H.-U.; Pittrow, D.; Beesdo-Baum, K.
Abstract : Aims: Although associations between various somatic diseases and depression are well established, findings concerning the role of gender and anxiety disorders for these associations remain fragmented and partly inconsistent. Combining data from three large-scaled epidemiological studies in primary care, we aim to investigate interactions of somatic diseases with gender and anxiety disorders in the association with depression. Methods: Self-reported depression according to the International Classification of Diseases, Tenth Edition (ICD-10) was assessed in n = 83 737 patients from three independent studies [DETECT (Diabetes Cardiovascular Risk Evaluation: Targets and Essential Data for Commitment of Treatment), Depression-2000 and Generalized Anxiety and Depression in Primary Care (GAD-P)] using the Depression Screening Questionnaire (DSQ). Diagnoses of depression, anxiety disorders and somatic diseases were obtained from treating physicians via standardised clinical appraisal forms. Results: In logistic regressions, adjusted for gender, age group and study, each somatic disease except for arterial hypertension and endocrine diseases was associated with self-reported depression (odds ratio, OR 1.3–2.6) and each somatic disease was associated with physician-diagnosed depression (OR 1.1–2.4). Most of these associations remained significant after additional adjustment for anxiety disorders and other somatic diseases. The associations with depression increased with a higher number of somatic diseases. Cardiovascular diseases (OR 0.8), diabetes mellitus (OR 0.8) and neurological diseases (OR 0.8) interacted with gender in the association with self-reported depression, while endocrine diseases (OR 0.8) interacted with gender in the association with physician-diagnosed depression. That is, the associations between respective somatic diseases and depression were less pronounced in females v. males. Moreover, cardiovascular diseases (OR 0.7), arterial hypertension (OR 0.8), gastrointestinal diseases (OR 0.7) and neurological diseases (OR 0.6) interacted with anxiety disorders in the association with self-reported depression, and each somatic disease interacted with anxiety disorders in the association with physician-diagnosed depression (OR 0.6–0.8). That is, the associations between respective somatic diseases and depression were less pronounced in patients with v. without anxiety disorders; arterial hypertension was negatively associated with self-reported depression only in patients with anxiety disorders, but not in patients without anxiety disorders. Conclusions: A range of somatic diseases as well as anxiety disorders are linked to depression – and especially patients with co-/multi-morbidity are affected. However, interactions with gender and anxiety disorders are noteworthy and of relevance to potentially improve recognition and treatment of depression by physicians. Somatic diseases are associated more strongly with depression in males v. females as well as in patients without v. with anxiety disorders, primarily because women and patients with anxiety disorders per se are characterised by considerably increased depression prevalence that only marginally changes in the presence of somatic comorbidity.